Comparison of Different Medical Treatment of Missed Abortion - Hashim Abid Alkareem, Israa; Jasim, Athraa (Tikrit Journal of Pharmaceutical Sciences, 2023)
Missed abortion constitutes a significant problem in gynecology patient, as itrepresents an unfortunate outcome of early pregnancy. Despites its frequencyhowever, there is still scope for improvement in patient care as it remains responsiblefor considerable emotional and psychological trauma to the patients. Aim of TheStudy:- This study is designed to evaluate for using misoprostol therapy in compareto other medical therapy for Iraqi female. Patients and Method:- The current studyrepresent a prospective clinical trial that was done on patients with missed abortion.The total number of cases that involving in the study were included 104 cases & 52 ofthem use mifepristone in a standard regimen and 52 use misoprostol in standardregimen, and those who failed to response from the two groups were selected to use acombination of these two drugs. Of these drugs misoprostol alone regimen was shownto be the most effective method for inducing complete abortion in 77.8% of thepatient using this drug alone within a shorter duration (<12 hours), and equal rate ofcomplication with other groups while mifepristone shows (55%) rate of completeabortion while the rate for combination of drugs was (43.6%). Other factors such asthe gestational age of the patient, types of delivery, Parity and the patient age werenot show to be significantly correlated with the end results. Conclusion:- The currentstudy found a significant correlation between the duration from the last delivery andthe end result, that complete miscarriage occurs more in patient delivered since morethan 11 months.